Paramolar tubercle in the left maxillary second premolar: a case report. - Carolina Rodríguez; Freddy Moreno (Dental Anthropology Association, 2006)
This is a case report describing a paramolar tubercle occurring on the buccal surface of left upper second premolar (tooth 25). From the perspective of dental anthropology, this morphological feature, though uncommon, may be useful for classification and identification.